2020
DOI: 10.1111/jam.14516
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of free or encapsulated selected phenylpropanoids against Escherichia coli and Staphylococcus epidermidis

Abstract: Aims Antibacterial activities of phenylpropenes (PPs) (eugenol, isoeugenol, estragole and trans‐anethole) and hydroxycinnamic acids (HCAs) (p‐coumaric, caffeic and ferulic acids) were assessed against Escherichia coli and Staphylococcus epidermidis. Effect of cyclodextrin and liposome encapsulation on the PPs activity was also evaluated. Methods and Results All PPs inhibited the bacterial growth in the hundred micromolar range, while HCAs did not, as determined by broth macrodilution. Anethole and estragole sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 66 publications
0
14
0
Order By: Relevance
“…The antimicrobial activity of savory is originated from carvacrol, thymol, and other monoterpenoid hydrocarbons (Miladi et al, 2013). A number of studies indicated the synergistic antibacterial effects of essential oils containing anethole, estragole, limonene, and carvacrol in combination together (Bassole & Juliani, 2012;Auezova et al, 2020). So, we can conclude that Bioessence ® is established upon compounds having an antimicrobial activity that can act as an alternative for antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…The antimicrobial activity of savory is originated from carvacrol, thymol, and other monoterpenoid hydrocarbons (Miladi et al, 2013). A number of studies indicated the synergistic antibacterial effects of essential oils containing anethole, estragole, limonene, and carvacrol in combination together (Bassole & Juliani, 2012;Auezova et al, 2020). So, we can conclude that Bioessence ® is established upon compounds having an antimicrobial activity that can act as an alternative for antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, in other cases, liposomal encapsulation resulted in decreased antimicrobial properties, as in the case of liposomes loaded with phenylpropenes (PPs) (eugenol, isoeugenol, estragole, and trans-anethole) that were assessed against E. coli and S. epidermidis. The decreased activity was then explained by prolonged retention of PPs in the liposomes that prevented their interaction with bacteria [49].…”
Section: Effect Of Liposome Preparation Methods On Antimicrobial Acti...mentioning
confidence: 99%
“…The strong antimicrobial activity of these essential oils might be due to synergistic effects of chemical constituent (both lipophilic and hydrophilic) present in the EOs, like β-caryophyllene [ 36 , 37 ], carvacrol [ 49 ], carvone [ 50 ], cembrene [ 51 ], eugenol [ 52 , 53 ], γ-terpinene, 1,8-cineole, α-terpinene [ 54 ], α-terpineol [ 55 ], α-Himachalene, α-Humulene [ 37 ], and (E)-Anethol [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…The essential oils were more effective against the Gram-positive strain than the Gram negative; it might be due to the presence of more lipophilic constituents in the essential oils. The strong antimicrobial activity of these essential oils might be due to synergistic effects of chemical constituent (both lipophilic and hydrophilic) present in the EOs, like β-caryophyllene [36,37], carvacrol [49], carvone [50], cembrene [51], eugenol [52,53], γterpinene, 1,8-cineole, α-terpinene [54], α-terpineol [55], α-Himachalene, α-Humulene [37], and (E)-Anethol [53].…”
Section: Antibacterial Activitymentioning
confidence: 99%